John Rae, Arctic explorer : the unfinished autobiography - Rae, John, 1813-1893 (Polynya Press, an imprint of University of Alberta Press, 2019)
"John Rae is best known today as the first European to reveal the fate of the Franklin Expedition, yet the range of Rae's accomplishments is much greater. Over five expeditions, Rae mapped some 1,550 miles (1,850 kilometres) of Arctic coastline; he is undoubtedly one of the Arctic's greatest explorers, yet today his significance is all but lost. John Rae, Arctic Explorer is an annotated version of Rae's unfinished autobiography. William Barr has extended Rae's previously unpublished manuscript and completed his story based on Rae's reports and correspondence--including reaction to his revelations about the Franklin Expedition. Barr's meticulously researched, long overdue presentation of Rae's life and legacy is an immensely valuable addition to the literature of Arctic exploration."--